Bleeding from the pancreatic cut surface post pancreaticoduodenectomy: a review of a tertiary referral centre. Issue 1 (11th November 2020) - Ackermann, Travis; Tan, Darius; Bowers, Kaye; Cullinan, Mark; Spilias, Dean; Croagh, Daniel; Berry, Roger
Abstract : Haemorrhage from the pancreatic cut surface after pancreaticoduodenectomy is uncommon. To our knowledge, this report describes the largest number of episodes of bleeding from the pancreatic cut surface post pancreaticoduodenectomy. We believe a soft pancreas, in addition to the acidic environment associated with pancreaticogastrostomy and the lack of tamponade associated with a dunking anastomosis, may explain the relatively high incidence of post‐pancreatectomy haemorrhage observed in this cohort. Abstract: Background: Haemorrhage from the pancreatic cut surface after pancreaticoduodenectomy is uncommon. The optimal treatment for post‐pancreatectomy haemorrhage (PPH) from the pancreatic cut surface remains controversial. Methods: We performed a retrospective analysis including all patients who underwent a pancreatiocoduodenectomy between 2008 and 2018 at a single tertiary institution in Melbourne, Australia, to analyse the incidence, potential risk factors, treatment and outcomes of cut surface PPH. Results: A total of 168 pancreaticoduodenectomies were performed during the study period with pancreaticogastrostomy being the most common method of reconstruction at our institution (84.5%). There were 12 instances of cut surface PPH (7.1%). The majority of cases of cut surface PPH occurred within 48 h following pancreaticoduodenectomy (67%) with 41.7% occurring in the first 24 h. All but one patient required surgical intervention but length of stay did not appear to be increased compared to those without cut surface PPH. There was a trend towards patients with cut surface PPH being more likely to have a non‐dilated pancreatic duct (75% versus 49%; P = 0.079). No significant differences were noted between patient with and without cut surface PPH with regards to abnormalities in platelet counts (3.2% versus 0%; P = 0.529), international normalized ratio (4.5% versus 8.3%; P = 0.694) and prophylactic anticoagulant administration or continuing antiplatelet use (28.2 versus 16.7%; P = 0.630). Conclusion: We believe that an unobstructed pancreas, in combination with the acidic environment associated with a dunking pancreaticogastrostomy anastomosis, may predispose to bleeding from the cut surface of the pancreas.